Black like me : representations of black women in advertisements placed in contemporary South African magazines. - Masina, Nomalanga Leander (My University, 2011)
Media analysis is used to investigate repetitive occurrences of dominant discourses circulating in the world. The recurring nature of periodicals such as magazines, allows research that tracks ideologies over time. The aim of this study was to uncover how black women’s representations in two women’s magazines indicated what normative roles the ideal readers were expected to play in their lives. I analysed representations of black women appearing in two South African magazines – True Love and Destiny. This analysis was situated within African feminist discourses, and utilised quantitative and qualitative research methods to unpack the types of representations present, and the frequency with which they occurred. The advertisements used appeared in the issues published between May 2009 and October 2009. From these I extracted 486 advertisements, 165 from Destiny and 321 in True Love. Critical Discourse Analysis informed the coding system that was used to analyse the meanings within the advertisements during the qualitative section of the research. Quantitative content analysis was then used to put a numerical description to the appearance of the codes, tracking the trends through time. I argue that the majority of images depicting black women in these advertisements privilege dominant heteronormative subjectivities. Interestingly, Destiny showed a wider variety of options available to the readership than True Love. My conclusion is that the representations with the highest rate of occurrence presented the subjugation of black women as the norm.